Kemampuan Guru Al-Qur’an Hadis Dalam Menerapkan Metode Pembelajaran di MTS Al-Washliyah Bangun Purba - Arlina Arlina; Siti Nur Khalifah; Siti Nurhalizah Sipahutar; Nurul Afrilliani Gajah; Mawaddatus Shifa (Intitut Agama Islam Nasional Laa Roiba Bogor, 2023)
The learning method is a systematic way of working that prioritizes the implementation of learning in the form of concrete implementation of certain steps, so as to create an effective learning process to achieve certain goals, for example achieving positive changes in students. The teacher as an educator is a determining factor for the success of an educational endeavor. In this case the researcher will examine the ability of Al-Qur'an hadith teachers to apply the discussion method in learning. The purpose of this research is that teachers can improve the quality of their learning in class, because if teachers are more familiar with learning methods, teachers will know more about various problems faced by students and more importantly teachers can make new innovations in their learning. In this study there are several types of interesting learning methods. The learning methods are 1. Lecture Method, 2. Discussion Method, 3. Question and Answer Method, and 4. Demonstration Method. The method used in this research is qualitative method. Then in data collection using the method of literature study, interviews, and observation, as well as data strengthening. Then the results of this discussion consist of 1) The ability of Al-Qur'an Hadith teachers in applying learning methods, 2) Barriers of Al-Qur'an Hadith Teachers in implementing learning methods, 3) Solutions made by Al-Qur'an Hadith Teachers in implementing learning methods. Keywords: Learning Methods, Teacher Ability